STUDENTS’ COMMUNICATION STYLE IN ENGLISH CLASS AT SMAN 1 SAKRA - Dina Muliana; Jumadil; Tri Setianingsih (Sinar Lima, 2025)
This research aimed to find what types of Students’ Communication Style in English Class At SMAN 1 SAKRA and what aspects that can affect students’ communication style in English Class At SMAN 1 SAKRA. This research used a qualitative research method. This research involved the 11th grade students of SMAN 1 SAKRA. There were approximately 35 respondents in Grade XI-C class of 2024. The result of Questionnaire and Document Checklist showed that there are two communication styles used by students in English class, namely Passive communication style and Assertive communication style. Where the total of Passive communication styles are 13 students (37.143%) and the total of Assertive communication styles are 22 students (62.857%). From the results of data analysis using personality test, questionnaires and document checklist, it was found that there are several aspects that can influence students' communication styles, namely in terms of Personality types showed that 80% extroverted that influenced Assertive Communication Style and 20% introverted that influenced Passive Communication style. And also 62,86% of students’ communication style influenced by Relationships, 20% influenced by Language Barriers and 51,43% influenced by Physical condition. Based on the findings, researcher expected to the teacher can create a safe and inclusive classroom environment where students feel comfortable to expressing their thoughts and opinions without fear of being judged or ridiculed, so students can develop their English learning strategies through their communication style.